Legal Certainty of Kidney Donor Rewards: A Comparative Perspective Between Indonesia and Iran - Tony Richard Alexander Samosir; Efa Laela Fakhriah; Sherly Ayuna Putri (Universitas Islam Sultan Agung, 2026)
This study examines the legal uncertainty surrounding the regulation of donor reward for kidney transplant donors in Indonesia, particularly concerning the distinction between the prohibition of organ commercialization and the provision of donor reward. Although Law Number 17 of 2023 concerning Health and Government Regulation Number 28 of 2024 have recognized donor rewards, both regulations fail to clearly regulate its form, value, and implementation mechanism, thereby creating normative ambiguity and the potential for illegal practices. This research employs a normative juridical method using statutory, conceptual, and comparative law approaches, with Iran serving as the comparative jurisdiction. The findings indicate that Indonesia continues to face a regulatory gap regarding operational arrangements, whereas Iran has implemented a structured donor support system under state supervision, despite ongoing ethical concerns. As a proposed solution, this study introduces the concept of measured reimbursement as a form of non-commercial donor reward through the reimbursement of direct and verifiable expenses, such as transportation costs and loss of income. This concept is expected to provide legal certainty, ensure protection for donors—particularly vulnerable groups—and prevent organ commercialization practices while remaining grounded in the principles of bioethics and social justice.